Annona muricata Leaf Extract Triggered Intrinsic Apoptotic Pathway to Attenuate Cancerous Features of Triple Negative Breast Cancer MDA-MB-231 Cells. (17th July 2018) - Kim, Jee Young; Dao, Thien T. P.; Song, Kwangho; Park, Sait Byul; Jang, Hyeri; Park, Min Kyoung; Gan, Soo Ueng; Kim, Yeong Shik
Abstract : Annona muricata L ., known as graviola, is an evergreen plant of the tropical regions and is a rich source of natural products. Graviola has various biological activities, and it is best known for its anticancer activity. This study aimed to investigate the effects of crude graviola extract in vitro on breast cancer cells; in particular, we aimed to identify an agent against triple negative breast cancer (TNBC). We used the TNBC MDA-MB-231 cell line as the experimental model and the ER(+) non-TNBC MCF-7 breast cancer cell line as the control. We identified annonaceous acetogenins, including annonacin isomers, characteristic to this plant by using liquid chromatography tandem mass spectrometry (LC/MS/MS). We observed a significant decrease in the cell viability in both cell lines within 48 h, whereas impaired cell motility and invasiveness were observed only in the MDA-MB-231 cell line. While the MCF-7 cells showed an ER-dependent mechanism of apoptosis, the apoptosis of MDA-MB-231 cells was governed by an intrinsic apoptotic pathway triggered by graviola leaf extract (GLE).